Effect of Music Medicine Intervention on Child `s Pain Level During Bone Marrow Aspiration and Lumber Puncture Procedures - Khalel, Myasar; Shawq, Adraa Hussein (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): To determine the effects of music therapy on the pain level of children who undergoing lumber puncture and bone marrow aspiration, and to find out the relationship between children’s pain and their socio-demographic characteristics during lumber puncture and bone marrow aspiration procedures.Methods: A quasi-experimental design, conducted among 78 school age children of both genders in Nineveh governorate at Ibn-AlAtheer teaching hospital, consisted of music (study) group and the routine treatment (control) group. Objective pain scale and physiological parameters were recorded. The data analyzed by computer programs (SPSS) and using descriptive statistics and independent samples (t-test).  Results: The result revealed high significant differences in child pain score and physiological parameters (mean, SD) between the study (1.42, 0.541) and control group (2.37, 0.594). The level of pain for study group was (25) mild, (13) moderate, and (2) sever. On the other hand, the level of pain for control group was (1, 22, 35) as mild, moderate, and sever pain respectively, and the t test significance for pain level was (0.001) at p-value 0.01.Conclusion: The music therapy intervention was effective in reducing the level of pain among children undergoing painful procedures (lumber puncture and bone marrow aspiration). This intervention can be used to decrease pain associated with invasive procedure and promote their compliance. Recommendations: This study recommended music therapy to be as one of the nurse-led non-pharmacological intervention that use recorded music in all medical procedure.